Core rod structure applied to winding type battery and lithium battery

By providing an insulating thermally conductive polymer coating on the outer surface of the core rod of the winding lithium battery, the damage caused by rigid contact between the core rod and the electrode sheet is solved, and the circulation performance and safety of the battery are significantly improved by improving the electrolyte infiltration effect and reserved circulating expansion space.

CN222801856UActive Publication Date: 2025-04-25ZHONGGU TIMES (BEIJING) NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202421703690.2
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-07-18
Publication Date
2025-04-25
Estimated Expiration
2034-07-18

AI Technical Summary

Technical Problem

The core rod and electrode sheet of the existing winding lithium battery are prone to damage the electrode sheet and the diaphragm after hot pressing, and the electrolyte is difficult to immerse the electrode sheet, resulting in low liquid retention volume of the core rod, poor circulation performance, and the absolute insulation of the core rod is not guaranteed, and it is easy to short-circuit corrosion.

Method used

An insulating thermally conductive polymer coating is provided on the outer surface of the mandrel main body. The coating is elastic and hydrophilic, improving the contact between the mandrel and the pole sheet, improving the wetting effect of the electrolyte, and reserves cyclic expansion space for the battery cell.

Benefits of technology

Through flexible contact, reduce pole sheet damage, improve the electrolyte infiltration effect, improve the cell liquid retention capacity, enhance insulation, prevent short circuits and corrosion, and improve the circulation performance and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222801856U_ABST
    Figure CN222801856U_ABST
Patent Text Reader

Abstract

The utility model relates to the technical field of lithium batteries, in particular to a core rod structure applied to a winding type battery and a lithium battery, the core rod structure comprises a core rod main body, the core rod main body is a hollow structure, the inner surface of the core rod main body is insulated, and the outer surface is provided with an insulated heat-conducting polymer coating; the insulating heat-conducting polymer coating is totally distributed on the outer surface or partially distributed along the length direction of the core rod main body; the lithium battery comprises the core rod structure and a roll core. According to the utility model, the elastic insulating heat-conducting polymer coating is additionally arranged, so that the rigid contact between the core rod and the pole piece is changed into flexible contact, and the pole piece and the diaphragm are prevented from being damaged; more importantly, the insulating heat-conducting polymer coating has certain hydrophilicity and swelling space, so that the infiltration effect can be improved, the liquid retention capacity of the battery cell can be improved, and an internal expansion space can be reserved in the later cycle period of the battery cell, thereby improving the cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to the technical field of lithium batteries, in particular to a core rod structure used for a winding type battery and a lithium battery. Background Art

[0002] A wound battery is also called a core-wound battery, in which a positive electrode sheet, a separator, and a negative electrode sheet are stacked in sequence and then wound to form a core-wound battery with a cavity. During the winding process, the positive electrode empty foil area and the negative electrode empty foil area extend out to form a positive electrode ear and a negative electrode ear at the end of the core-wound battery. A core rod is provided in the cavity, and the core and the core rod constitute a battery cell. The core rod provides structural support for the battery cell. The battery cell is loaded in a shell and sealed and fixed by the end cover assemblies at both ends of the shell.

[0003] like Figure 2 The figure shows the mainstream wound square case battery on the market. It is rectangular in shape as a whole. The flat oval core (left) made by winding is placed in the stamped shell (right) along the height direction of the battery. The positive and negative poles and the pressure relief valve are all located on the top of the battery. The middle of the flat oval core is provided with Figure 2 The hollow structure of the core rod shown. The applicant has also launched a new core rod wound battery, including: a winding core, a cover plate assembly, a temperature control channel interface and a shell, etc.; the winding core, the cover plate assembly, the temperature control channel interface and the shell are connected to form the battery; the winding core includes: a hollow pipe (core rod), a positive electrode sheet, a first diaphragm, a negative electrode sheet and a second diaphragm; the positive electrode sheet, the first diaphragm, the negative electrode sheet and the second diaphragm are stacked in sequence and wound in the center on the hollow pipe to form the winding core; a positive electrode ear is provided on one side of the positive electrode sheet of the winding core, and a negative electrode ear is provided on one side of the negative electrode sheet of the winding core, and the positive electrode ear and the negative electrode ear are located at the opposite ends of the hollow pipe (core rod) when stacked and wound.

[0004] However, whether it is the mainstream wound battery in the market or the new core rod wound battery proposed by the applicant, the core rod and the pole piece are tightly fitted after hot pressing, and the rigid contact is very likely to damage the pole piece and the diaphragm; moreover, the winding structure is dense as a whole, and the gap between the winding core and the shell is small. After the electrolyte is injected from the top or bottom of the shell, it is difficult for the electrolyte to infiltrate the pole piece, the pole piece infiltration effect is poor, the core rod has low liquid retention, the internal electrolyte volume is small, and the cycle performance is poor. In addition, the core rod cannot be guaranteed to be absolutely insulated, and it is easy to short-circuit corrosion.

[0005] To this end, this application is filed. Utility Model Content

[0006] In view of the above-mentioned shortcomings of the prior art, the utility model provides a core rod structure and a lithium battery applied to a wound battery.

[0007] In order to achieve the above-mentioned purpose, the main technical solutions adopted by the utility model include:

[0008] On the one hand, the utility model proposes a core rod structure for a wound battery, including a core rod body, wherein the core rod body is a hollow structure, the inner surface of which is insulated, and the outer surface is provided with an insulating thermally conductive polymer coating, and the insulating thermally conductive polymer coating is fully distributed on the outer surface or partially distributed along the length direction of the core rod body.

[0009] In this embodiment, the insulating thermally conductive polymer coating is obtained by any method including but not limited to coating, spraying, in-situ polymerization, electrostatic adsorption, adhesion, and any other existing or future coating obtaining methods.

[0010] In this embodiment, the material of the mandrel body includes but is not limited to any one or more of aluminum, copper, zinc, magnesium, steel, chromium, and titanium, and is preferably formed by integral extrusion.

[0011] In this embodiment, the inner surface of the core rod body is insulated, and the insulation treatment method includes but is not limited to oxidation, electroplating, spraying, coating, laser treatment, vapor deposition, and any other existing or future insulation treatment methods. The provision of the insulation layer can not only reduce the direct contact between the core rod and other conductive parts inside the battery to avoid short circuits, but also play a certain protective role on the battery cell, preventing the battery cell from mechanical damage or chemical corrosion during the charging and discharging process, and reducing the unstable performance of the battery due to current fluctuations or abnormalities during the charging and discharging process, thereby extending the service life of the battery.

[0012] Compared with the prior art, the utility model provides an insulating thermally conductive polymer coating on the outer surface of the core rod body, and the presence of the coating has at least the following beneficial effects:

[0013] (1) The coating is elastic. The elastic coating changes the rigid contact between the core rod and the pole piece into a flexible contact, effectively alleviating and avoiding the damage of the pole piece after hot pressing;

[0014] (2) The coating has a certain degree of hydrophilicity, and thus has different degrees of adsorption on the electrolyte, which helps to improve the wetting effect and increase the liquid retention of the battery cell;

[0015] (3) The coating has a swelling space, which can reserve internal expansion space for the battery cell cycle and ensure the battery cell cycle effect;

[0016] Therefore, the core rod structure proposed in the utility model can significantly enhance the electrolyte infiltration effect, increase the electrolyte retention capacity of the battery cell, and has good insulation properties, can effectively prevent battery cell damage caused by short circuit and electrochemical corrosion, has good safety, and the resulting battery has good cycle performance.

[0017] Preferably, the inner wall and the outer wall of the mandrel body have the same cross-sectional shape and are concentric, and the cross-sectional shape is one of a circle, a triangle, a rectangle, a pentagon, a hexagon, and an octagon. That is, the mandrel body is selected from any one of a hollow triangular prism, a quadrangular prism, a pentagonal prism, a hexagonal prism, and an octagonal prism, and the wall thickness of each prism is uniform and consistent everywhere.

[0018] More preferably, when the mandrel body is a prismatic structure, the edges and corners of the prismatic structure are transitioned by an arc.

[0019] In this embodiment, the edges and corners with arc transition help to reduce the gap between it and the core, making the internal structure of the battery compact and consistent, improving the energy density and cycle performance of the battery, and can also prevent piercing the diaphragm or other sensitive components inside the battery, reducing stress concentration, and increasing heat dissipation.

[0020] Even more preferably, the mandrel body is a hollow quadrangular prism, the length of the quadrangular prism is denoted as L1, the thickness is denoted as H1, and the width is denoted as T1, 10 mm ≤ L1 ≤ 2000 mm, 10 mm ≤ H1 ≤ 200 mm, 10 mm ≤ T1 ≤ 200 mm; the edges and corners are transitioned by an arc with a radius R1, 0 < R1 ≤ 100 mm; the length of the insulating and heat-conducting polymer coating is denoted as L0, and the thickness is denoted as H0, 1 mm ≤ L0 ≤ 2000 mm, 0.1 mm ≤ H0 ≤ 200 mm.

[0021] Still more preferably, the thickness H0 of the insulating and heat-conducting polymer coating is 1% - 20% of the thickness H1 of the mandrel body, and the length of the insulating and heat-conducting polymer coating is 95% - 100% of the length of the mandrel body.

[0022] Even further preferably, the thickness H0 of the insulating and heat-conducting polymer coating is 10% of the thickness H1 of the mandrel body, and the length of the insulating and heat-conducting polymer coating is 98% of the length of the mandrel body.

[0023] We found that the thickness of the polymer coating should not be too thin or too thick. If it is too thin, the damage to the electrode and the diaphragm is not significantly improved. If it is too thick, the adhesion stability between the coating and the mandrel is poor, and it is easy to crack or even fall off. Moreover, a too thick coating will sacrifice the structural strength of the mandrel to a certain extent and deteriorate its supporting ability. Through creative labor, we confirmed that the thickness H0 of the polymer coating is preferably 1% - 20% of the thickness H1 of the mandrel body, most preferably 10%, and the length of the polymer coating is 95% - 100% of the length of the mandrel body, most preferably 98%.

[0024] Preferably, the outer perimeter of the cross-section of the quadrangular prism perpendicular to the length direction of the quadrangular prism is 25 - 175 mm, and 150 mm is the best; the wall thickness of the quadrangular prism is 0.5 - 10 mm, and 5 mm is the best.

[0025] In this embodiment, the quadrangular prism not only improves the electrolyte infiltration effect, but also has a large structural support strength and a relatively stable positioning effect. On the automated production line, it can cooperate with automated equipment to realize the automatic unwinding and winding of positive and negative electrode sheets and diaphragms, and ensure the uniformity of the internal structure of the wound battery, reduce the risk of short circuits caused by misalignment, and improve the safety performance of the battery.

[0026] Preferably, the insulating thermally conductive polymer coating is selected from any one of a polyvinylidene fluoride coating, a polyethylene oxide coating, a polyimide coating, and a polyurethane coating.

[0027] In this embodiment, polyvinylidene fluoride PVDF, polyethylene oxide PEO, polyimide PI, and polyurethane PU all have good electrical insulation and thermal conductivity, which can not only effectively prevent the adverse effects of short circuit and electrochemical corrosion, but also improve the thermal conductivity of the core rod, accelerate heat conduction, evenly distribute temperature, reduce thermal stress, enhance the heat dissipation performance of the battery, and improve cycle stability.

[0028] In this embodiment, polyvinylidene fluoride PVDF, polyethylene oxide PEO, polyimide PI, and polyurethane PU all have a certain degree of hydrophilicity. Under the thickness and length specified in the utility model (the thickness H0 of the polymer coating is 1%-20% of the thickness H1 of the core rod body, and the length of the polymer coating is 95%-100% of the length of the core rod body), their coatings will have a proper adsorption effect on the electrolyte, which helps to fully infiltrate the electrolyte, increase the liquid retention of the battery cell, and ultimately improve the various performances of the battery cell and the battery.

[0029] In this embodiment, in order to further improve the hydrophilicity of the polymer, polyvinylidene fluoride, polyethylene oxide, polyimide, and polyurethane may also be first modified to enhance their hydrophilicity, and then attached to the outer surface of the core rod by any existing or future coating formation method such as coating, spraying, in-situ polymerization, electrostatic adsorption, adhesion, etc. However, the corresponding thickness and length need to be adaptively improved, which is not further explored in this application.

[0030] On the other hand, the utility model also proposes a lithium battery, which contains a winding core and the core rod structure as described above, and the winding core and other components of the battery are all made of conventional technical means in the field.

[0031] Preferably, the ratio of the outer circumference of the cross section of the winding core perpendicular to the length direction of the winding core to the outer circumference of the cross section of the mandrel perpendicular to the length direction of the mandrel body is 2-15.

[0032] In this embodiment, the core rod that meets the above conditions can be easily inserted into and fix the core, ensuring that the core after winding can fit tightly against the core rod, the core rod will not loosen and can support the deformation and stress of the core during the winding process, which helps to reduce gaps and stress concentration during the winding process and improve the uniformity and stability of the core.

[0033] Compared with the prior art, the utility model adds an elastic insulating and thermally conductive polymer coating. When the electrode is wound into a core, the rigid contact between the core rod and the core is changed to flexible contact, thereby avoiding damage to the electrode and the diaphragm and improving the thermal conductivity of the core rod; more importantly, the insulating and thermally conductive polymer coating has hydrophilic groups and swelling space, which can improve the wetting effect, increase the liquid retention of the battery cell and reserve internal expansion space in the later stage of the battery cell cycle, thereby improving the cycle performance, solving the problems in the prior art that the electrolyte is difficult to infiltrate the electrode after the core is loaded into the shell, the electrode wetting effect is poor, the core rod liquid retention is low, the internal electrolyte amount is small, and the cycle performance is poor. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0035] Figure 1 This is a schematic structural diagram of Example 1 of the utility model.

[0036] Figure 2 It is the mainstream wound square shell battery on the market. DETAILED DESCRIPTION

[0037] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0038] Example 1

[0039] A core rod structure for a wound battery comprises a hollow core rod body, the core rod body is a quadrangular prism, the edges and corners of the quadrangular prism are transitioned by arcs, the inner surface of the quadrangular prism is insulated, and the outer surface is provided with a polyvinylidene fluoride coating, and the polyvinylidene fluoride coating is distributed on the outer surface along the length direction of the quadrangular prism;

[0040] The length L1 of the quadrangular prism is 250mm, the thickness H1 is 30mm, the width T1 is 45mm, the outer circumference of the quadrangular prism section is 150mm, the wall thickness of the quadrangular prism is 5mm, and the transition arc R1 of the corners is 5mm; the length L0 of the polyvinylidene fluoride coating is 245mm, the thickness H0 is 0.5mm, and the polyvinylidene fluoride coating is located at 245mm in the center of the quadrangular prism.

[0041] The utility model also provides a lithium battery, which comprises a winding core and the core rod structure as described above, wherein the outer circumference of the winding core cross section is 1200 mm, which is 8 times the outer circumference of the quadrangular prism cross section.

[0042] The preparation process of the core is as follows: the mass ratio of the positive electrode material system is the active material Li(Ni 0.9 Co 0.05 Mn 0.05 )O2: conductive agent carbon nanotube: conductive agent Super P: binder PVDF = 98: 0.5: 0.5: 1, the current collector is a 12μm thick carbon-coated aluminum foil, the positive electrode material system is slurried, coated, and rolled to obtain a positive electrode sheet; the negative electrode material system mass ratio is active material carbon black: conductive agent Super P: dispersant carboxymethyl cellulose: binder styrene butadiene rubber = 96.3: 1: 1.2: 1.5, the current collector is a 6μm thick copper foil, the negative electrode material system is slurried, coated, and rolled to obtain a negative electrode sheet; the positive electrode sheet and the negative electrode sheet are wound and shaped with a 12μm thick ceramic-coated polyethylene diaphragm to obtain a winding core. The winding core is welded to the cover, put into the shell, sealed, welded, dried, injected, and formed to obtain a lithium battery, and the electrolyte uses 1M LiPF6 (the solvent is ethylene carbonate and diethyl carbonate in a volume ratio of 1: 1).

[0043] Example 2

[0044] Compared with Example 1, the thickness of the polyvinylidene fluoride coating is 0.05 mm, and the rest is consistent with Example 1.

[0045] Example 3

[0046] Compared with Example 1, the thickness of the polyvinylidene fluoride coating is 0.2 mm, and the rest is consistent with Example 1.

[0047] Example 4

[0048] Compared with Example 1, the thickness of the polyvinylidene fluoride coating is 1 mm, and the rest is consistent with Example 1.

[0049] Example 5

[0050] Compared with Example 1, the length of the polyvinylidene fluoride coating is 250 mm, and the polyvinylidene fluoride coating completely covers the outer surface of the quadrangular prism. The rest is consistent with Example 1.

[0051] Example 6

[0052] Compared with Example 1, the length of the polyvinylidene fluoride coating is 238 mm and is located at 238 mm in the middle of the length direction of the quadrangular prism, and the rest are consistent with Example 1.

[0053] Example 7

[0054] Compared with Example 1, the polyvinylidene fluoride coating is adjusted to a polyethylene oxide coating of equal thickness and length, and the rest is consistent with Example 1.

[0055] Example 8

[0056] Compared with Example 1, the polyvinylidene fluoride coating is adjusted to a polyimide coating of equal thickness and length, and the rest is consistent with Example 1.

[0057] Example 9

[0058] Compared with Example 1, the polyvinylidene fluoride coating is adjusted to a polyurethane coating of equal thickness and length, and the rest is consistent with Example 1.

[0059] Example 10

[0060] A core rod structure for a wound battery comprises a hollow core rod body, the core rod body is a cylinder, the inner surface of the cylinder is insulated, and the outer surface is provided with a polyvinylidene fluoride coating, and the polyvinylidene fluoride coating is distributed on the outer surface along the length direction of the cylinder;

[0061] The length of the cylinder is 250 mm, the outer diameter is 45 mm, the outer circumference of the cylindrical section is 141.3 mm, and the wall thickness is 5 mm; the length L0 of the polyvinylidene fluoride coating is 245 mm, the thickness H0 is 0.5 mm, and the polyvinylidene fluoride coating is located at 245 mm in the center of the cylinder.

[0062] The utility model also provides a lithium battery, which comprises a winding core and the core rod structure as described above, wherein the outer circumference of the winding core cross section is 1413 mm, which is 10 times the outer circumference of the cylindrical cross section.

[0063] Comparative Example 1

[0064] Compared with Example 1, the outer surface of the quadrangular prism is not provided with a polyvinylidene fluoride coating.

[0065] Comparative Example 2

[0066] Compared with Example 10, the outer surface of the cylinder is not provided with a polyvinylidene fluoride coating.

[0067] Comparative Example 3

[0068] Compared with Example 1, the thickness of the polyvinylidene fluoride coating is 0.01 mm, and the rest is consistent with Example 1.

[0069] Comparative Example 4

[0070] Compared with Example 1, the thickness of the polyvinylidene fluoride coating is 2 mm, and the rest is consistent with Example 1.

[0071] Comparative Example 5

[0072] Compared with Example 1, the length of the polyvinylidene fluoride is 230 mm and is located at 230 mm in the middle of the length direction of the quadrangular prism, and the rest are consistent with Example 1.

[0073] The core rod structures obtained in each embodiment and comparative example were respectively assembled into test batteries, and electrochemical performance tests were carried out. After the tests, the battery cells were disassembled to observe whether the battery cells were damaged and the states of the pole pieces and diaphragms after disassembly. The liquid injection effect and liquid retention effect were qualitatively analyzed by color difference.

[0074] The specific operation of the test is: 0.33C rate charge, 0.33C rate discharge, test voltage range 2.8V-4.3V, temperature 17-27℃, relative humidity 10%-90%, atmospheric pressure 86-106kPa, and test the number of cycles with its capacity not less than 80%.

[0075] After observation and testing:

[0076] (1) With the same liquid injection volume, compared with Comparative Example 1, the liquid injection time required for Examples 1 to 9 is shortened to varying degrees, and the liquid retention volume is increased to varying degrees, and the liquid retention effect is relatively good. After disassembling Comparative Example 1, it was found that the battery cell was bruised, while no visible damage was observed in the battery cells of Examples 1 to 9.

[0077] Furthermore, it was measured that the number of cycles for which the capacity of the test battery assembled in Comparative Example 1 was not less than 80% was 3356 times, while the number of cycles of Examples 1 to 10 was between 4253 and 6134 times, especially Example 1, which had the highest number of cycles, up to 6134 times.

[0078] The present application found that the thickness and distribution of the polyvinylidene fluoride coating have a significant impact on the performance of the battery. The thickness of the polyvinylidene fluoride coating of Comparative Example 1, Comparative Example 3, Example 2, Example 3, Example 1, Example 4, and Comparative Example 4 are 0, 0.01mm, 0.05mm, 0.2mm, 0.5mm, 1mm, and 2mm, respectively. The test shows that the corresponding number of cycles is 3356, 3401, 4253, 4898, 6134, 5480, and 3902, respectively. After disassembly, it is found that the battery cells of Comparative Example 1 and Comparative Example 3 are damaged. It can be seen that the problem of damage to the pole piece or battery cell cannot be solved if the polyvinylidene fluoride coating is not provided or the thickness of the polyvinylidene fluoride coating is too small; when the thickness is 0.05mm-1mm, the cycle performance is relatively high, and the thickness below 0.05mm or above 1mm is not conducive to the improvement of the cycle performance, and within this range, the obtained lithium battery capacity is relatively high, generally above 550Ah. The lengths of the polyvinylidene fluoride in Comparative Example 5, Example 6, Example 1, and Example 5 are 230 mm, 238 mm, 245 mm, and 250 mm, respectively, and the ratios to the core rod length are 92%, 95%, 98%, and 100%, respectively. Tests show that the number of cycles of Example 6, Example 1, and Example 5 are 4654, 6134, and 5670, respectively. Although the battery cell of Comparative Example 6 has no damage, the liquid injection effect and liquid retention effect are poor, and there is leakage, and the cycle performance test cannot be carried out. Compared with 98% coating, the liquid injection effect and liquid retention effect of full coating are better when observed with the naked eye, and there is no battery cell damage phenomenon, but the cycle performance of full coating is obviously not as good as 98% coating.

[0079] Furthermore, from the comparison of Example 1, Example 7, Example 8, Example 9 with Comparative Example 1, it can be seen that the four polymer coatings of polyvinylidene fluoride coating, polyethylene oxide coating, polyimide coating, and polyurethane coating can promote the infiltration of electrolyte and obtain better liquid injection effect and liquid retention effect. However, in terms of cycle performance, polyvinylidene fluoride coating is better, and the number of cycles of the other polymer coatings is lower than that of polyvinylidene fluoride to varying degrees. The number of cycles reflects the comprehensive performance of lithium batteries. Obviously, the use of polyvinylidene fluoride helps to improve the comprehensive performance of lithium batteries.

[0080] (2) Compared with Comparative Example 2, with the same injection volume, the injection time required for Example 10 is shortened, the liquid retention volume is increased, and the liquid retention effect is improved. After disassembly, it is found that the battery cells of Comparative Example 2 are damaged, while no visible damage is observed in the battery cells of Example 10. After testing, the number of cycles of Comparative Example 2 is 3520 times, while the number of cycles of Example 10 is 6023 times. It is obvious that the polyvinylidene fluoride coating on the outer surface of the cylindrical core rod can significantly improve the cycle performance of the lithium battery.

[0081] In summary, the core rod structure proposed in the utility model can significantly enhance the electrolyte infiltration effect, increase the electrolyte retention capacity of the battery cell, and has good insulation properties, can effectively prevent battery cell damage caused by short circuit and electrochemical corrosion, has good safety, and the resulting battery has good cycle performance.

[0082] Although the embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. A person skilled in the art may change, modify, replace and deform the above embodiments within the scope of the present invention. In addition, a person skilled in the art may combine and combine different embodiments or examples described in this specification and features of different embodiments or examples without contradiction.

Claims

1. A core rod structure for a wound battery, characterized in that: It includes a mandrel body which is of a hollow structure. Its inner surface is insulated, and an insulating and heat-conducting polymer coating is provided on its outer surface. The insulating and heat-conducting polymer coating is fully distributed on the outer surface or partially distributed along the length direction of the mandrel body.

2. The core rod structure for a wound battery according to claim 1, characterized in that: The cross-sectional shapes of the inner wall and the outer wall of the mandrel body are the same and their centers coincide. The cross-sectional shape is any one of a circle, a triangle, a rectangle, a pentagon, a hexagon, and an octagon.

3. The core rod structure for a wound battery according to claim 2, characterized in that: When the mandrel body is a prismatic structure, the edges and corners of the prismatic structure are transitioned with arcs.

4. The core rod structure for a wound battery according to claim 3, characterized in that: The mandrel body is a hollow quadrangular prism. The length of the quadrangular prism is denoted as L1, the thickness is denoted as H1, and the width is denoted as T1. 10 mm ≤ L1 ≤ 2000 mm, 10 mm ≤ H1 ≤ 200 mm, 10 mm ≤ T1 ≤ 200 mm; the edges and corners are transitioned with an arc of radius R1, 0 < R1 ≤ 100 mm; the length of the insulating and heat-conducting polymer coating is denoted as L0, and the thickness is denoted as H0. 1 mm ≤ L0 ≤ 2000 mm, 0.1 mm ≤ H0 ≤ 200 mm.

5. The core rod structure for a wound battery according to claim 4, characterized in that: The thickness H0 of the insulating and heat-conducting polymer coating is 1% - 20% of the thickness H1 of the mandrel body, and the length of the insulating and heat-conducting polymer coating is 95% - 100% of the length of the mandrel body.

6. The core rod structure for a wound battery according to claim 5, characterized in that: The thickness H0 of the insulating and heat-conducting polymer coating is 10% of the thickness H1 of the mandrel body, and the length of the insulating and heat-conducting polymer coating is 98% of the length of the mandrel body.

7. The core rod structure for a wound battery according to claim 4, characterized in that: The outer perimeter of the cross-section of the quadrangular prism perpendicular to the length direction of the quadrangular prism is 25 - 175 mm, and the wall thickness of the quadrangular prism is 0.5 - 10 mm.

8. The core rod structure for a wound battery according to any one of claims 1 to 7, characterized in that: The insulating and heat-conducting polymer coating is selected from any one of a polyvinylidene fluoride coating, a polyethylene oxide coating, a polyimide coating, and a polyurethane coating.

9. A lithium battery, characterized in that: It contains a core and a mandrel structure according to any one of claims 1 - 8.

10. The lithium battery according to claim 9, characterized in that: The ratio of the outer perimeter of the cross-section of the core perpendicular to the length direction of the core to the outer perimeter of the cross-section of the mandrel body perpendicular to the length direction of the mandrel body is 2 - 15.